THE IMPORTANCE OF THE PATIENT’S SPIRITUALITY / RELIGIOSITY IN CARE GIVEN BY PHYSICIANS RESIDENTS OF THE MUNICIPAL MEDICAL RESIDENCE PROGRAM IN FAMILY AND COMMUNITY MEDICINE IN THE MUNICIPALITY OF PRAIA GRANDE - SP - da Silva Souza, Daniel (Health and Society, 2023)
The aim of this study was to analyze, through an online questionnaire, how the resident physicians of the Municipal Residency Program in Family and Community Medicine in Praia Grande/SP perceive and act in relation to the spirituality and religiosity of the patients in the service. To this end, a bibliographical study and an interactive literature review on the theme of spirituality and religiosity (E/R) in clinical practice were carried out, in addition to the application of an online questionnaire to resident physicians, together with a free consent form. and clarified. Through the online questionnaire, we sought to analyze, in addition to demographic data, quantitative and qualitative data that describe the experience with the E/R theme of the 33 respondent resident physicians. Most physicians were female (78.8%), aged between 25 and 30 years (78.8%), second-year residents (54.5%), graduated between 2016 and 2022, and active in zone 3 (54.5%). Most respondents had no religion (31%), did not consider themselves a religious person (39.4%), but considered themselves a spiritual person (57.6%). Still, most approach the E/R theme a few times with the patient (51.5%), but do it mainly when the patient is affected by a serious illness, encouraging them in their E/R practices, in addition to agree that E/R influences the patient’s health and healing process. Finally, most respondents did not have training related to the E/R theme (66.6%), not even training during the Family and Community Medical Residency (78.8%). Thus, it is concluded that, although they do not consider themselves religious or have a religion, there is a concern among residents of Family and Community Medicine in Praia Grande/SP for comprehensive patient care, which must include spiritual and religious aspects.